Zerumbone nanoparticle preparation and characterization - Rahman, Heshu; Abdullah, Rasedee; Bustaman, Ahmad (Lambert Academic Publishing, 2015)
The Zingiberaceae family of plants is found in tropical and subtropical areas and approximately 161 species from 18 genera of this family are found in Peninsular Malaysia. The plant species belonging to the Zingiberaceae family have been reported to possess biological activities responsible for its medicinal value. The ginger rhizome is generally recognized as safe and it is used traditionally in local folklore medicine for various ailments. Zingiber zerumbet (L.) Smith belonging to this family is an edible ginger, originating from South-East Asia and been cultivated for thousands of years. Generally, the rhizomes and the leaves are used for spice, tea, beverages and medical purposes, while the milky, mucilaginous substance of the pinecones are as shampoo and natural hair conditioner, especially in Asia and Hawaii contained several types of phytochemicals and the rhizome, in particular, has been used in traditional Oriental medicine for various human ailments in different parts of the globe, especially for the treatment of digestive condition.